Evaluation of Anemia and Blood Transfusions in Critically Ill Patients - Murat Bağcı; Perihan Ergin Özcan; Evren Şentürk; Lütfi Telci; Nahit Çakar (Galenos Yayinevi, 2014)
Objective: In follow up of critically ill patients that are in intensive care unit (ICU), the effects of anemia on morbidity and mortality are controversial and transfusion threshold values vary in studies. In our study, we purposed to assess approach and transfusion practice in anemia existence in critically ill patients. Material and Method: In our study that was planned prospectively and observationally, 167 patients staying in İstanbul Faculty of Medicine ICU between 15 May 2008-15 November 2008 were included. Low hemoglobin (62.7%) was found to be a major reason for transfusions and nearly 90% of them were made in first three days. In our unit, daily blood amount for analysis purposes was found to be 19.2 ml. per ICU. In our study, however pretransfusion Hb value was found to be 7.6, two third of transfusions was made when Hb value was between 7-10. Results: In ICU, it was found that the patients underwent transfusion stayed longer than the other patients and their mortality rates were higher. Mortality rates were found to be increased more and more, as erythrocyte suspension transfused to patients increased. Furthermore, we think that even this phlebotomy amount that we found contributes anemia negatively, in parallel with the information in the literature. It was observed that most transfusion decisions were applied with the decisions that physician made with clinic approach special to patient and threshold Hb value were not cared. Conclusion: physicians should regard patients' individual compensation and tolerance capacities and determine transfusion indication. The most appropriate point should be determined regarding risks and benefits of transfusion as well as its immunological and inflammatory its results.